Adrenergic regulation of cancer immunity - Jingjing Zhu; Pierre-Hubert Desimpel; Constance Gérard; Benoit J. Van den Eynde (Clinical Cancer Research, 2026)
Abstract The nervous and immune systems engage in extensive bidirectional crosstalk that shapes tumor progression and therapeutic response. Among the neuro-immune pathways involved in cancer, adrenergic receptor signaling has emerged as a key regulator of the tumor microenvironment. In this review, we summarize current understanding of the distinct roles of β- and α2-adrenergic receptor signaling in cancer immunity and their therapeutic implications. β2-adrenergic receptor signaling promotes immune suppression by impairing dendritic cell cross-presentation, inhibiting CD8⁺ T cell and natural killer (NK) cell function, driving T cell exhaustion, and enhancing regulatory T cell and myeloid-derived suppressor cell activity. Consistent with these mechanisms, retrospective studies and meta-analyses involving more than 600,000 patients have associated β-blocker use with survival benefits in several cancers. In contrast, recent preclinical studies demonstrate that α2-adrenergic receptor agonists induce potent anti-tumor immunity in immunocompetent murine models, including checkpoint-resistant tumors, through CD4⁺ and CD8⁺ T cell-dependent mechanisms. Together, these findings identify adrenergic signaling as a promising and pharmacologically tractable target in cancer immunotherapy and support further translational and clinical investigation.